Skovoroda`s images and motives in the works of Hanna Barvinok - Matushek, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The task of our article is to consider Skovoroda’s images and motives, in particular heart and happiness, in the works of Oleksandra Bilozers’ka-Kulish.Discourse analysis seems to be an appropriate method of research, since it allows us to build a chain of texts on one topic and find out the peculiarities of its detection at each stage, taking into the current contexts. This approach is quite productive and relevant for modern literary criticism, as it allows us to confirm or refute conclusions about the stadiality of Ukrainian literature, the continuity of the literary process, the sources of creativity of a particular author, etc.The article discusses the images and motives of the stories of Hanna Barvinok, which are key in the philosophical concept of Hrygoriy Skovoroda. This is the image of the heart and the motive of happiness. The works of Hanna Barvinok are studied in a broad literary and cultural context, which includes the works of M. Kovalyns`kyy, H. Danylevs`kyy, P. Kulish, M. Sumtsov, D. Bagaliy and others.The author of the article came to the conclusion that in the second half of the nineteenth century, the perception of the figure of H. Skovoroda in the Ukrainian cultural space acquired certain features: he became known as the author of philosophical and literary works. His live was an example of his moral and philosophical doctrine. He represented the Ukrainian man with his image.There are various images of happy people in the works of Hanna Barvinok. These are those who live with God and according to His rules, and those who have a favorite work, and those who had an experience a high feeling of love. The heroes of the works of this author are emotional, mostly with traditional concepts of human happiness.It should be noted that really happy are those characters who combine Christian commandments in their behavior and are guided by their heart.The heart is the main means of character formation and an indicator of the picture of their world in the texts of Hanna Barvinok. And this just corresponded to the teachings of H. Skovoroda.